Students' Mistakes and Misconceptions on the Subject of Conics - Sudihartinih, Eyus; Purniati, Tia (International Journal of Education, 2020)
The purpose of this study is to determine the levels of geometric thinking, mistakes, and misconceptions of students on the concept of conics. This study was conducted on 91 students in the first semester in 2017 at one of the universities in Indonesia. Data were collected using written tests, interviews, and documentation. From the test results, the students' answers were divided into correct and incorrect solutions. Interviews and documentation were used to analyze level of geometric thinking nd student misconception. As a result, the misconceptions found were (1) the students could not determine the two possible simple equations, (2) the students could not determine the description of a simple parabola equation, (3) the students could not determine the conics equation, (4) the students could not prove the length of the latus rectum of an ellipse, (5) the students could not determine a simple equation of asymptote of hyperbola, while its vertices point were known, and (6) the students could not determine the equations of hyperbola focus and the difference between the length of the radius of the focus was known. Students who experienced mistakes and misconceptions were still at the first level of the van Hiele geometric thinking model.